Plasmodesmata without callose and calreticulin in higher plants – open channels for fast symplastic transport? - Demchenko, Kirill N.; Voitsekhovskaja, Olga V.; Pawlowski, Katharina (Frontiers in Plant Science, 2014)
Plasmodesmata (PD) represent membrane-lined channels that link adjacent plant cells across the cell wall. PD of higher plants contain a central tube of endoplasmic reticulum called desmotubule. Membrane and lumen proteins seem to be able to move through the desmotubule, but most transport processes through PD occur through the cytoplasmic annulus (Brunkard et al., 2013). Calreticulin (CRT), a highly conserved Ca2+-binding protein found in all multi-cellular eukaryotes, predominantly located in the ER, was shown to localize to PD, though not all PD accumulate CRT. In nitrogen fixing actinorhizal root nodules of the Australian tree Casuarina glauca, the primary walls of infected cells containing the microsymbiont become lignified upon infection. TEM analysis of these nodules showed that during the differentiation of infected cells, PD connecting infected cells, and connecting infected and adjacent uninfected cells, were reduced in number as well as diameter (Schubert et al., 2013). In contrast with PD connecting young infected cells, and most PD connecting mature infected and adjacent uninfected cells, PD connecting mature infected cells did not accumulate CRT. Furthermore, as shown here, these PD were not associated with callose, and based on their diameter, they probably had lost their desmotubules. We speculate that either this is a slow path to PD degradation, or that the loss of callose accumulation and presumably also desmotubules leads to the PD becoming open channels and improves metabolite exchange between cells.